Perilaku Sosial Masyarakat dalam Melestarikan Kearifan Lokal: (Studi Kasus Tradisi Merti Desa Mbah Bregas di Dusun Ngino, Kalurahan Margoagung, Kapanewon Seyegan, Kabupaten Sleman) - Bresca Merina; Suyatno Suyatno (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
The purpose of this study is to determine how the social behavior of the Margoagung Village Community, especially Ngino Hamlet, in preserving local wisdom inherited from the ancestors of Mbah Bregas, especially in building community harmony. This field research was conducted using a qualitative descriptive method. This research was conducted by taking a case study in Ngino Hamlet, Margoagung Village, Seyegan Sub-district, Sleman Regency from June to July 2025. The informants of this study were the leaders, committees, traditional figures and all parties involved and witnessed directly the Merti activities of Margoagung Village. Data collection was carried out through observation, interviews and documentation. Data analysis was carried out through four stages, namely: data documentation, data reduction, data presentation, and drawing conclusions/verification. The study findings show that the entire series of Merti activities of Mbah Bregas Village, Margoagung Village build community harmony through participation, cooperation and mutual cooperation without distinguishing religion, ethnicity, race, social strata and profession.